2022
DOI: 10.1002/glia.24144
|View full text |Cite
|
Sign up to set email alerts
|

MAC2 is a long‐lasting marker of peripheral cell infiltrates into the mouse CNS after bone marrow transplantation and coronavirus infection

Abstract: Microglia are the primary resident myeloid cells of the brain responsible for maintaining homeostasis and protecting the central nervous system (CNS) from damage and infection. Monocytes and monocyte-derived macrophages arising from the periphery have also been implicated in CNS pathologies, however, distinguishing between different myeloid cell populations in the CNS has been difficult. Here, we set out to develop a reliable histological marker that can assess distinct myeloid cell heterogeneity and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 103 publications
1
12
0
Order By: Relevance
“…Both microglia and infiltrating myeloid cells exhibit phagocytic activities, and because the latter were shown to express microglia‐specific markers upon differentiation in brain parenchyma, defining the cell type responsible for phagocytic uptake of infected neurons has been difficult [ 74 ]. The current work supports the results of recent studies that Gal3 is a specific marker of infiltrating monocytes [ 49 ]. Moreover, our work revealed that a large fraction of infiltrating myeloid cells remained Iba1 negative at least within the first few days of residing in brain parenchyma.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both microglia and infiltrating myeloid cells exhibit phagocytic activities, and because the latter were shown to express microglia‐specific markers upon differentiation in brain parenchyma, defining the cell type responsible for phagocytic uptake of infected neurons has been difficult [ 74 ]. The current work supports the results of recent studies that Gal3 is a specific marker of infiltrating monocytes [ 49 ]. Moreover, our work revealed that a large fraction of infiltrating myeloid cells remained Iba1 negative at least within the first few days of residing in brain parenchyma.…”
Section: Discussionsupporting
confidence: 92%
“…To confirm these results, brains of hAβ mice challenged IC with McKrae were examined using immunostaining for Galectin 3 (Gal3, also known as MAC2 or LGALS3). Gal3 was recently shown to be a specific, long‐lasting marker of infiltrating myeloid cells [ 49 ]. Coimmunostaining using anti‐Gal3 and a‐HSV1 antibodies revealed massive infiltration by Gal3‐positive cells into brain areas affected by the virus (Figure 12A ).…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that SCF+G-CSF treatment may change the transcriptional profiles from one cell class to the other cell class. We found that the transcriptome in this cell cluster showed greater overlap with Mo/Mac reference datasets than with microglia datasets and included robust expression of the Mo/Mac marker Lgals3 [86]. Our findings also open the possibility that a subset of Mo/Mac that migrates to the brain following SCF+G-CSF treatment takes on a microglia transcriptional profile.…”
Section: Discussionmentioning
confidence: 72%
“…the syndromes modeled in mice infected with rhabdovirus (vesicular stomatitis virus) [13], flaviviruses (eg. West Nile virus) [42], or the neurotropic coronavirus, JHM mouse hepatitis virus [26], share common features implicated in triggering microglia activation [14]. They each infect neurons and inflict substantial neuronal damage; they each target astro- and/or oligodendrocytes for infection and cytopathogenic damage; they induce peripheral monocytic infiltration in the CNS.…”
Section: Discussionmentioning
confidence: 99%